2021
DOI: 10.3390/land10101055
|View full text |Cite
|
Sign up to set email alerts
|

An Effectiveness Study on the Use of Different Types of LID for Water Cycle Recovery in a Small Catchment

Abstract: Low-Impact Development (LID) is alleviating the water cycle problems that arise from an increasing impervious surface area caused by urbanization. However, there is insufficient research on the application and analyses of LID techniques that are used for studying the management goals for water cycle restoration. The present study applied various LID techniques, utilizing the stormwater management model (SWMM) in the Naju-Noan Waterfront Zone Construction Project and studying its effects, aiming to restore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…However, when the rainfall intensity is too high, the soil infiltration rate in permeable pavement area is close to the minimum value (soil is close to the state of full saturation), and the mitigating effect of permeable pavement on runoff is reduced. Therefore, the total runoff of the other three scenarios gradually approaches or even exceeds that of No-PP, which is consistent with many research findings on the impact of permeable pavement (a type of low-impact development (LID) facility) on runoff [4,46].…”
Section: Function Analysis Of Stormwater Management Facilities In Zhu...supporting
confidence: 89%
“…However, when the rainfall intensity is too high, the soil infiltration rate in permeable pavement area is close to the minimum value (soil is close to the state of full saturation), and the mitigating effect of permeable pavement on runoff is reduced. Therefore, the total runoff of the other three scenarios gradually approaches or even exceeds that of No-PP, which is consistent with many research findings on the impact of permeable pavement (a type of low-impact development (LID) facility) on runoff [4,46].…”
Section: Function Analysis Of Stormwater Management Facilities In Zhu...supporting
confidence: 89%
“…Several studies have confirmed that LIDs (Sustainable Drainage Systems, SUDs) have a positive impact on the hydrological and hydraulic load of traditional urban drainage systems; however, the biggest reduction was achieved in cases of small, relatively frequent rainfall events and more pervious soil types [199][200][201][202][203][204]. In case of extreme rainfall events, such a reduction in flow (water volume) is very limited and sensitive to local conditions.…”
Section: Rainfall-runoff Models and The Decision-making Processmentioning
confidence: 99%
“…In addition, LID hydrological performances at different spatial scales have been assessed to support their adoption as a solution to control stormwater in urban watersheds (Yang et al., 2020). However, the evidence of LID effectiveness at the watershed scale is limited (Andrés‐Doménech et al., 2018; Kim & Kim, 2021). Therefore, questions remain about how LID practices can individually or cumulatively affect urban watershed hydrology.…”
Section: Introductionmentioning
confidence: 99%